Development of a SYBR Green real-time PCR-based assay system for detection of Neisseria gonorrhoeae - Andi Yasmon; Rela Febriani; Louisa Ivana Utami; Fithriyah Fithriyah; Yeva Rosana; Fera Ibrahim; Pratiwi Sudarmono (Universitas Gadjah Mada, 2022)
Diagnosis of Neisseria gonorrhoeae infection is needed for patient therapy and for reducing this bacterial transmission in the population. The culture method is a gold standard method for N. gonorrhoeae detection, however it has low sensitivity. Among molecular methods with high sensitivity and specificity, SYBR Green real-time PCR is the potential method for N. gonorrhoeae detection. In this study, we developed an SYBR Green real-time PCR-based system assay for N. gonorrhoeae detection. Several PCR conditions were optimized and analyzed including primer annealing temperature, DNA template volume, the limit of detection (LoD), cross-reaction with others (bacteria, viruses, fungus, protozoa), and quality assurance. The results showed that the annealing temperature and DNA template volume were 60oC and 5 µL, respectively. The LoD was 29 DNA copies corresponding to 3 bacterial cells per reaction. No cross-reaction was detected for other bacteria, viruses, fungus and protozoa. The external quality assurances enrolled in 2019 and 2021 showed 100% concordance. The preliminary testing for clinical samples was also 100% concordance. In conclusion, the SYBR Green real-time PCR-based system assay developed in this study is promising for application in clinical laboratories.